2017
DOI: 10.1007/s13205-017-0794-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of phytoremediation ability of Coriander sativum for soil and water co-contaminated with lead and arsenic: a small-scale study

Abstract: A study was conducted to access the phytoremediation potential of Coriandrum sativum for lead (Pb) and Arsenic (As). Metal tolerance index and pot experiment were conducted. Viable seeds were spread on filter paper and planted in soil placed in pots. The amount of Pb and As in control and in tailing soil was 0.27, 0.141, 1.77, and 0.35 ppm. The study was carried out in triplicates for a period of 4 weeks under natural conditions. The physico-chemical properties of soil were determined using the standard method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The study recommended that the whole plant of coriander from seeds, leaves, and stalks seems to be a promising natural chelating agent for toxic heavy metals. 13 The data may be supported by those reported by Donia who found that coriander increased the serum levels of vasodilator factors (PGI2, NO, and eNOS), decreased Na+ retention and serum uric acid (UA) level, and ameliorated glucolipid profiles in highfructose and high-salt diet-induced hypertension by mitigating abnormal changes in vascular endothelial function, renal and intestinal sodium absorption, glucolipid homeostasis, and gut microbiota in rats. 48…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The study recommended that the whole plant of coriander from seeds, leaves, and stalks seems to be a promising natural chelating agent for toxic heavy metals. 13 The data may be supported by those reported by Donia who found that coriander increased the serum levels of vasodilator factors (PGI2, NO, and eNOS), decreased Na+ retention and serum uric acid (UA) level, and ameliorated glucolipid profiles in highfructose and high-salt diet-induced hypertension by mitigating abnormal changes in vascular endothelial function, renal and intestinal sodium absorption, glucolipid homeostasis, and gut microbiota in rats. 48…”
Section: Discussionsupporting
confidence: 55%
“…8 Different types of extracts from different parts of the plant have been shown to exhibit pharmacological effects, including, antioxidant, cardioprotective and antatherosclerotic effects in diabetic patients, growth promoting and improved carcass yield in broilers, stomachic and aphrodisiac effects, and antidote for heavy metals as arsenic and mercury. [9][10][11][12][13] The present study was designed to evaluate the antihyperlipidemic effect of C. sativum seed extract (CSSE) in albino rats fed on high-fat diet. To fulfil this aim, the following objectives have been conducted: the effect of CSSE on lipid biomarkers as total cholesterol, triglycerides and lipoproteins; the effect of CSSE on biomarkers indicating hepatic (total protein, bilirubins, aminotransferases), renal (urea, creatinine, uric acid) and cardiac (creatine kinasemyoglobin biomarker, troponin-I) dysfunction; and the qualitative phytochemical analysis of CSSE to determine the active principles underlying its effect.…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption capacity and efficiency of coriander in removal of Pb 2+ , Cd 2+ ions and turbidity from simulated contaminated water was reported [25]. Additionally, C. sativum plants showed considerable potential for phytoremediation of Pb and As from contaminated soil and water [26].…”
Section: Discussionmentioning
confidence: 99%
“…In order to evaluate the phytotoxic effects, the lengths of the roots and shoots of plants subjected to different concentrations of pollutants are measured. The tolerance index or elongation rate is calculated by relating the lengths of the roots/shoots of the pollutant samples to the lengths of the roots/shoots of the blank sample [27,28] (Eq. 3).…”
Section: Tolerance Index or Elongation Rate For Roots And Shoots (Er %)mentioning
confidence: 99%